1982
DOI: 10.1038/bjc.1982.211
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypovitaminosis C in lung-cancer patients: the utilization of vitamin C in surgical repair and lymphocyte-related host resistance

Abstract: Summary.-Plasma and buffy-coat vitamin C were estimated in 158 samples from 139 lung-cancer patients, at all stages of the disease. Most samples showed hypovitaminosis C in both estimations: 64% had plasma, and 25% buffy-coat values below the thresholds for incipient clinical scurvy (0.3 mg% and 10 jg/108 cells respectively).Levels were diet-dependent and could be increased by oral supplements. Levels were low both in tumour-bearing patients and in those clinically free of disease after resection. The latter h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
6

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 22 publications
1
50
0
6
Order By: Relevance
“…21 Green tea extract and its derivatives have shown to exert inhibitory effects against bladder tumor growth; researchers at the Medical College of Ohio observed 100% cell lethality in AY-27 rat transitional cell cancer following exposure to EGCG, and in vivo, histology showed 64% tumor-free rate in Fisher 344 rats exposed to EGCG over the control. 22 Ascorbic acid has been reported to exert cytotoxic and antimetastatic actions on malignant cell lines; [23][24][25] in addition, low levels of ascorbic acid have been reported in cancer patients. [26][27][28] Our previous studies indicated that the synergistic anticancer effect of ascorbic acid, proline, lysine and EGCG on several cancer cell lines in tissue culture studies was greater than that of the individual nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…21 Green tea extract and its derivatives have shown to exert inhibitory effects against bladder tumor growth; researchers at the Medical College of Ohio observed 100% cell lethality in AY-27 rat transitional cell cancer following exposure to EGCG, and in vivo, histology showed 64% tumor-free rate in Fisher 344 rats exposed to EGCG over the control. 22 Ascorbic acid has been reported to exert cytotoxic and antimetastatic actions on malignant cell lines; [23][24][25] in addition, low levels of ascorbic acid have been reported in cancer patients. [26][27][28] Our previous studies indicated that the synergistic anticancer effect of ascorbic acid, proline, lysine and EGCG on several cancer cell lines in tissue culture studies was greater than that of the individual nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…These changes include uptake of the vitamin by the tumour (Anthony & Schorah, 1982), and alterations in the metabolism of the vitamin by the tumour (Rivlin, 1973). CoA is the metabolically-active form of pantothenate and our data suggest that growth of these tumours affects pantothenate metabolism in the host.…”
Section: Discussionmentioning
confidence: 82%
“…In this study the nutritional status of 70% of the patients on supplements did not deteriorate, whilst it worsened in 80% of patients on un-supplemented diet. In a case study involving lung cancer patients, 64% displayed serum vitamin C levels below the threshold associated with development of scurvy [5]. In contrast, surgically resected lung cancer tissues contained higher levels of vitamin C compared with normal adjacent tissue [6].…”
Section: Nutritional Status Of Cancer Patientsmentioning
confidence: 99%